Cinema and Politics: Social Alliances vs Entrenched Stereotypes, Collective Action and Actual Solidarity, in the Movie “Pride" - Papadakis, Nikos (HAPSc Policy Briefs Series, 2024)
The present paper attempts a critical review of the movie “Pride” (2014), namely the film by Matthew Warchus on the, less known, story of the beginning of the LGSM- Lesbians and Gay Support the Miners’ initiative and subsequently the LGΒT+ community’s activism, that has resulted in a, rather unexpected, social alliance with the National Union of Mineworkers, during the (major and long-lasting) Miners’ strike in UK, against Tories’ and M. Thatcher’s Government strict measures and their overall neoliberal policy (1984-1985). The focus of the paper is on the political content of the Movie. Thus, it emphasizes issues of collective action, actual solidarity, (in praxi) deconstruction of entrenched and embedded stereotypes, as well as of individual emancipation, as (brilliantly) raised and depicted in the movie. The analysis also considers the broader historical and socio- political context.